REPRESENTASI LOGO ASURANSI JIWA BERSAMA BUMIPUTERA 1912 SEBAGAI BENTUK IDENTITAS PERUSAHAAN - Elsa Dhamayanti June; Tantri Puspita Yazid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The insurance business competition more stringent, demanding parties service Insurance company program provider to review thinking return mission and business strategy good, then it is possible the company will Losing hearts of competition. AJB Bumiputera 1912 using the logo change of strategy development. Changing the logo mean change the image and that's an opportunity to review the management for improve the company's image in the eyes of the competitors. Where the AJB Bumiputera1912 this has lot of rivals such as Life Insurance, Foreign-Owned Insurance And other private owned also, in order to bring a fresh impression and is not oldies so, AJB Bumiputera parties to replace the old logo as a Form of Coorporate Identity. The Objective knows signs meaning, objects, intepretant of Life Insurance logo with Bumiputera 1912.The Research using qualitative research methods and backed with analysis theory of semiotics of Charles Sanders Pierce. The subject research is determined by purposive sampling technique which consists differences and divisions of public relations division commuication Part Of AJB Bumiputera 1912. The data collection techniques include interviews, observation, documentation and analysis framework. The analaysis used the tachniques based analysis of researchers (the argument researchers) wich is based on concepts and a theories that are relevant. Data analysis technique used is the analysis of semiology The Charles Sanders Peirce with triadic model, where signs, objects and Interpretations have meet each other relationships and excess with strength checks the validity of data is done using triangulation techniques.The Results of research is indicates From logo 1912 is overall from all signs the elements in hearts the basic foundation logo 1912 What has meaning symbolizes power, dignity and strength, object of logo life insurance with Bumiputera 1912. A sign of the minds of thought of record logo for the review creates logos a new and interpretan from logo life insurance with Bumiputera 1912 are from purport of everything process of achieving the sense of delivered by a shape signs, and the elements contained in this logo is a logo that is intrepretation life insurance along with Bumiputra 1912. Key word: representation, logo, analysis semiotics, corporate indetity.